Approximation of continuous functions with random errors in observed values - Savkina, M. Yu. (Ukrains’kyi Matematychnyi Zhurnal, 1998)
We consider the problem of approximation of continuous functions by generalized polynomials in the case where the values of the function at the observation points are known with random errors. We construct confidence limits with a given significance level for the true values of the function at any point of its domain of definition.